Operative Versus Conservative Management of Displaced Tibial Shaft Fracture in Adolescents. Issue 7 (October 2016) - Kinney, Matthew C.; Nagle, David; Bastrom, Tracey; Linn, Michael S.; Schwartz, Alexandra K.; Pennock, Andrew T.
Abstract : Background: Displaced tibial shaft fractures are common in adolescent patients, yet there is no standardized management strategy. We compared surgical fixation and closed reduction and casting (CRC) of these fractures to assess treatment outcomes and determine predictors of failure. Methods: We retrospectively reviewed all patients aged 12 to 18 who presented with a displaced tibial shaft fracture that required reduction over an 8-year period. Exclusion criteria included open fractures and lack of follow-up to radiographic union or to 6 months from the index procedure. Fractures were initially treated based on surgeon preference either with CRC or with immediate intramedullary nailing. Seventy-four patients met inclusion criteria: 57 were initially managed with CRC and 17 with operative fixation. Radiographic healing was defined as bridging of 3 cortices and adequacy of final alignment was defined as <5 degrees of angular deformity in both planes and <1.0 cm of shortening. Outcomes were analyzed both on intent-to-treat principles and by definitive treatment method. Results: Although all fractures in both groups achieved bony healing, 23 of the 57 patients who underwent CRC failed closed treatment and ultimately required surgery (40.3%). Multivariate analysis of patient and fracture characteristics revealed fracture displacement of >20% (odds ratio=7.8, P <0.05) and the presence of a fibula fracture (odds ratio=5.06, P =0.05) as predictors of closed treatment failure. Patients ultimately managed with intramedullary nailing trended toward increased adequacy of final alignment (92.5% vs. 72.4%, P =0.10) but required longer hospitalization (5.4 vs. 1.9 d, P <0.001) and had a higher incidence of anterior knee pain (20% vs. 0%, P <0.01). There was no significant difference between groups with respect to time to healing. Conclusions: Treatment outcomes between initial operative fixation and closed reduction of displaced tibia fractures in adolescents are similar, but patients must be counseled about the high failure rates with CRC. Predictors of CRC failure include initial fracture displacement and the presence of a fibula fracture—these variables should be considered when selecting a treatment method. Level of Evidence: Level III—Therapeutic study.